Management of Normogonadotropic males with idiopathic infertility with bilateral varicocelectomy with and without intramuscular recombinant FSH and HCG course(s): A twenty-year- experience in a prospective, controlled, and randomized clinical study (British Journal of Multidisciplinary and Advanced Studies, 2023)
This study presents a clinical prospective double-blinded study that contains three groups of infertile males with normogonadotropic oligoasthenospermia. All groups A, B, and C were operated on for their bilateral varicoceles. The first included 152 patients who were only operated for bilateral varicocele (nominated group A). The second group of 237 patients constituted those who were operated on, with fertile female partners, and whose preoperative spermogram showed a count lower than 15 million/ml and a 3-hour-motility lower than 20%. This group constituted two categories based on their treatment. Therefore, groups B and C received postoperative courses of intramuscular injections of recombinant follicle-stimulating hormone (rFSH) and human chorionic gonadotropin (HCG), i.e., group B received one course (3 months), and group C received two courses (6 months). The main objective is to determine the improvement in the postoperative seminal parameters in the different groups. The sample constituted 391 infertile males who were recruited conveniently based on their willingness to share their progress information and were also informed that they could stop their participation freely with no questions asked. In our treated patients, in both groups B and C, who received 1 or 2 courses of rFSH and HCG, spontaneous pregnancy occurred in 69 patients and 52 patients, respectively. Likewise, assisted pregnancy occurred in 28 and 19 patients, respectively. So treated males of groups B and C resulted in 91/140 (65%) and 61/96 (63.54%) live offspring, respectively.